Analysis of Nurse Services Quality on Patient Satisfaction Class II Hospital - Ofsilin Drawanizai; Mappeaty Nyorong (Hasanuddin Medan, 2022)
Nursing services are the most critical factor in determining the extent to which hospital service quality is assessed. If patients are satisfied, the nursing service will bring satisfaction and comfort, and vice versa. The number of complaints filed in the suggestion box grows annually, rising from 45 in 2019 to 52 in 2020 (15%), particularly concerned with nurses' ability to deliver nursing services The purpose of the study was to determine how service quality affects the satisfaction of Class III inpatients at Latersia Hospital Binjai. This was cross-sectional research conducted as part of an analytic survey. The population was 101 people, and the samples were 80 people. A questionnaire was used to collect data. The chi square test was used to assess the data univariate, bivariate, and multivariate at a 95% significant level. The findings revealed that while the dependability of nursing services was good (53.8%), the responsiveness (52.5%), assurance (55%), empathy (58.8%), and physical evidence (66.3) were not. Patients were not satisfied with nursing services (51.2%). Statistically, reliability (0.013), responsiveness (0.007), empathy (0.000), assurance (0.001), and physical evidence (0.002) in the Class III Inpatient Room had a substantial impact on patient satisfaction The findings revealed that nurse services had an impact on Class III inpatient satisfaction in terms of reliability, responsiveness, assurance, empathy, and physical proof. It is recommended that hospital management improve overall control of health services and give patient comfort support facilities, especially in Class III rooms.